Thick Description Analysis of Solo Keroncong Music as Indonesiaâ€™s Cultural Diplomacy - Danis Sugiyanto; Denik Iswardani Witarti; Komarudin Subekti; Christophe Moure (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2026)
This research examines keroncong music as a representation of Javanese culture. The aim of the research was to interpret the lyrics of keroncong in a cultural context using thick description, Clifford Geertz. Keroncong music is also seen from a cultural diplomacy perspective. Research data was obtained from interviews and direct observation and supported by relevant literature. This research explicitly analyzes canonical songs such as Bengawan Solo, Tirtonadi, Taman Jurug, and Kota Solo to understand how cultural symbols are produced and consumed. Research data were obtained through participant observation, in-depth interviews, and focus group discussions (FGD) with a community of practitioners. Lyric analysis is integrated with High-Context Communication (HCC) theory to demonstrate how the indirect communication patterns of Javanese society are represented in keroncong musicality. The research found Javanese cultural symbols in the lyrics of keroncong songs. It highlights the city of Solo as the center of cultural civilization on the island of Java. Solo is known as â€œthe spirit of Java.â€ The keroncong lyrics, which tell stories about people's lives, are able to attract and inspire love for Indonesia. Indonesian cultural diplomacy is supported by a community of keroncong music lovers abroad who act as diplomatic agents. The beauty of keroncong's musicality and poetic lyrics becomes a cultural signpost that is considered a soft power in cultural diplomacy. The conclusion of this research confirms that the rich culture of the Indonesian nation can be developed as an important instrument of cultural diplomacy. The success of cultural diplomacy requires direct contact with communities of Indonesian arts and culture lovers, at home and abroad.Keywords: Cultural diplomacy, keroncong, keroncong, soft power, thick descriptionÂ ABSTRAKPenelitian ini mengkaji musik keroncong sebagai representasi budaya Jawa. Tujuan penelitian dilakukan untuk menerjemahkan lagu-lagu keroncong dalam konteks budaya dengan menggunakan thick description, Clifford Geertz. Musik keroncong juga dilihat dari perspektif diplomasi budaya. Penelitian ini secara eksplisit menganalisis lagu-lagu kanonik seperti Bengawan Solo, Tirtonadi, Taman Jurug, dan Kota Solo untuk memahami bagaimana simbol-simbol budaya diproduksi dan dikonsumsi. Data penelitian diperoleh melalui observasi partisipan, wawancara mendalam, dan diskusi kelompok terfokus (FGD) dengan komunitas praktisi. Analisis lirik diintegrasikan dengan teori High-Context Communication (HCC) untuk menunjukkan bagaimana pola komunikasi tidak langsung masyarakat Jawa direpresentasikan dalam musikalitas keroncong. Data penelitian diperoleh dari hasil wawancara, observasi langsung, dan didukung pustaka yang relevan. Penelitian menemukan simbol-simbol budaya Jawa dalam lirik lagu keroncong. Hasil analisis terhadap lagu-lagu keroncong dalam penelitian ini menonjolkan kota Solo sebagai pusat peradaban budaya di pulau Jawa, dikenal dengan istilah â€œthe spirit of Java.â€ Lirik lagu keroncong yang bercerita tentang kehidupan masyarakat mampu menarik dan menimbulkan kecintaan terhadap Indonesia. Diplomasi budaya Indonesia didukung oleh adanya komunitas pecinta musik keroncong di luar negeri yang berperan sebagai agen diplomasi. Keindahan musikalitas keroncong dan lirik yang puitis menjadi soft power dalam diplomasi budaya. Kesimpulan penelitian ini menguatkan bahwa kekayaan budaya bangsa Indonesia dapat dikembangkan sebagai instrumen penting diplomasi budaya. Kesuksesan pelaksanaan diplomasi budaya memerlukan jalinan langsung dengan para komunitas pecinta seni dan budaya Indonesia, di dalam dan luar negeri.Kata Kunci: Diplomasi budaya, keroncong, soft power, thick description